Cyclic changes of the junctional zone on 3 T MRI images in young and middle-aged females during the menstrual cycle. Issue 4 (April 2016) - He, Y.L.; Ding, N.; Li, Y.; Li, Z.; Xiang, Y.; Jin, Z.Y.; Xue, H.D.
Abstract : Aim: To evaluate the cyclic changes of the junctional zone in different age groups during the menstrual cycle using 3 T magnetic resonance imaging (MRI), and to investigate the correlation with basic female hormone levels. Materials and methods: Thirty-eight normal volunteers (age range, 20–40 years; mean age, 29 years: 20–30 years, n =22; 31–40 years, n =16) with regular menstrual cycles underwent a pelvic 3 T MRI examination on the 2nd or 3rd days of their menstrual phase (MP), follicular phase (FP), peri-ovulatory phase (OP), and luteal phase (LP), respectively, including a T2-weighted three-dimensional (3D) turbo spin-echo (TSE) with variable flip angle ("SPACE") sequence, a T2-weighted mapping sequence, and diffusion tensor imaging (DTI). The thickness, T2, fractional anisotropy (FA), and apparent diffusion coefficient (ADC) values of the junctional zone on mid-sagittal images were separately measured by two radiologists on the post-processed workstation. The linear mixed model and one-way analysis of variance were used to evaluate the differences between the two age groups during the four phases. The serum levels of oestradiol (E), progesterone (P), luteinising hormone (LH), and follicle-stimulating hormone (FSH) were measured during the MP and compared with anatomical and functional MRI values using Pearson's correlation analysis. Results: The thickness of the anterior and posterior junctional zone increased with age ( p <0.05). In the 20–30 year age group, during the MP the junctional zone was significantly thicker than at the other three phases ( p <0.05). Serum E levels correlated moderately with variation in thickness during the menstrual cycle. In the 30–40 year age group, no statistical difference in the thickness was found during the menstrual cycle. As age increased, the ADC values of the junctional zone decreased ( p =0.02). In both groups, the ADC and T2 values of the junctional zone showed significant differences between the MP and LP ( p <0.05), whereas no statistical difference in FA values were found during the menstrual cycle. Serum E, P, and LH levels correlated moderately with variation of ADC and T2 values during the menstrual cycle. Conclusions: The thickness and ADC values of the junctional zone showed significant differences between the two age groups. Cyclic changes in the thickness, ADC, and T2 values of the junctional zone were found during the menstrual cycle, which correlated moderately with the serum female hormone levels. Highlights: A prospective multi-sequences MRI study on the junctional zone of 38 volunteers during four phases of the menstrual cycle. Thickness and ADC values of the junctional zone showed significant differences between two age groups. Changes of the thickness, ADC and T2 values during menstrual cycle were moderately correlated with female hormone levels. It is of great importance to realize the variation of the junctional zone in the different physiological states to investigate junctional zone related gynecological diseases.